Politics of Occupation-Centred Practice : Reflections on Occupational Engagement across Cultures - Pollard, Nick, MSc(OT); Sakellariou, Dikaios; Wiley eBooks (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
"Politics of Occupation-Centred Practice addresses the cultural aspects of occupational identity and draws out the implications for practice, moving beyond the clinical environment to include the occupational therapist's work in the wider community"--Provided by publisher.
The language of occupation / Nick Pollard and Dikaios Sakellariou -- Occupational literacy / Nick Pollard and Dikaios Sakellariou -- A grammar for a language of occupation / Nick Pollard and Dikaios Sakellariou -- Towards a transformational grammar of occupation / Nick Pollard and Dikaios Sakellariou -- Narratives of recognition / Dikaios Sakellariou and Nick Pollard -- Narratives and truths / Dikaios Sakellariou and Nick Pollard -- Occupation in a Greek town : flowing, emergent, flexible across time and space / Sarah Kantartzis, Matthew Molineux, and Sally Foster -- Indigenous Ainu occupational identities and the natural environment in Hokkaido / Mami Aoyama -- People with disabilities and participation : experiences and challenges of an occupational therapy practice in the city of São Paulo, Brazil / Sandra Maria Galheigo [and others] -- Communities of Writing / Nick Pollard -- Disability, sexuality, and intimacy / Pamela Block [and others] -- Models and Human Occupation / Nick Pollard and Neil Carver -- Participation, Time, Effort, and Speech Disability Justice / Devva Kasnitz and Pamela Block -- A society founded on occupation / Nick Pollard and Dikaios Sakellariou.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Occupational therapy; Cross-Cultural Comparison; Occupations; Politics; Socioeconomic Factors; Work; MEDICAL -- Health Risk Assessment; Occupational therapy; Electronic books